Impact of Moringa oleifera Meal (MOM) Inclusion in Diet on Haemato-Biochemical Profile of Growing Surti Kids - Pandey, Anushri; Modi, Rakesh J; Lunagariya, Pravin M; Islam, Manzarul (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present research work was intended to assess the haemato-biochemical profile of 6-8 months old 18 growing Surti kids by utilizing the three diverse concentrations of Moringa oleifera meal (0%, 25% and 50%) by weight premix in concentrate part of feed. The diets were offered for 14 weeks to the experimental kids, which were randomly divided into three groups of six kids each, i.e., 4 females and 2 males in each group. The haemato-biochemical parameters were measured individually at the beginning (Day 0), mid (Day 49) and end (Day 98) of the experiment. Results showed that haemoglobin and serum total protein, ALT (Alanine transaminase), AST (Aspartate transaminase), urea, glucose, calcium and phosphorus showed no significant difference, while serum creatinine, catalase, and SOD (Superoxide dismutase) activity differed significantly (p
Keywords: Moringa oleifera meal (MOM); Haemato-biochemical profile; Surti kids